Preeclampsia association of placental nucleotide variations in eNOS, VEGFA, and FLT-1 genes in Latin American pregnant women. (April 2023) - Macías-Salas, Alejo; Sosa-Macías, Martha; Barragán-Zúñiga, Laura Jazel; Blanco-Castañeda, Ricardo; Damiano, Alicia; Garcia-Robles, Reggie; Ayala-Ramírez, Paola; Bueno-Sánchez, Julio; Giachini, Fernanda Regina; Escudero, Carlos; Galaviz-Hernández, Carlos
Abstract: Introduction: Preeclampsia is a leading cause of maternal and fetal morbidity in low- and middle-income countries, including those in Latin America. Placental vascular alterations are crucial in the pathophysiology of preeclampsia and few studies have evaluated nucleotide variations on genes associated with vascular regulation in the human placenta. This study aimed to evaluate whether placental nucleotide variations on eNOS, VEGFA, and FLT-1 genes are more frequently associated with preeclampsia in the Latin American population. Methods: This case-control study included placental tissue from 88 controls and 82 cases that were genotyped through Taqman probes for eNOS, VEGFA, and FLT-1 genes. The intergroup comparisons were analyzed with the Mann-Whitney U test. Genotype and allele frequencies were compared by the X 2 test. The association between the nucleotide variants with preeclampsia was evaluated through logistic regression analysis. Results: A significant association was observed for VEGFA SNV rs2010963 (OR 1.95; CI 95% 1.13–3.37), after adjusting for population substructure. The allele combination T, G, G, C, C, C (rs2070744, rs1799983, rs2010963, rs3025039, rs699947 and rs4769613 respectively), showed a negative association with preeclampsia (OR 0.08; CI 95% 0.01–0.93). results. Discussion: Placental SNV rs2010963 in the VEGFA gene was a risk factor for preeclampsia, while the allele combination T, G, G, C, C, C may represent potential protective factors for preeclampsia within Latin American women. Highlights: SNVs on placental vascular-related genes (VRG) are associated with preeclampsia. Allele combinations on placental SNVs in VRG might be protective for preeclampsia. Placenta l eNOS, VEGFA and FLT1 genes act in an epistatic way. The at risk or protective nature of a SNV is influenced by ethnicity.